EFFICACY OF SEVERAL MULTIPLE LIQUID BIOFERTILIZERS ON THE GROWTH AND PRODUCTION OF SWEET CORN (Zea mays L. saccharata) - Yaumalika, Mutiara; Rahayu, Arifah; Adimihardja, Sjarif Avitidjadi (JURNAL AGRONIDA, 2017)
This study was aimed at assessing the efficacy of several multiple liquid biofertilizers found in the market on the growth and production of sweet corn. A factorial completely randomized design was used. The first factor was the type of multiple liquid biofertilizers (PHMC) consisting of three levels, namely PHMC 1, PHMC 2, and PHMC 3. The second factor was synthetic fertilizer rates consisting of five levels, namely 0, 25, 50, 75, and 100% of recommended rate (R). Results showed that the application of PHMC 3 combined with synthetic fertilizer treatments (05 R and 25% R) significantly increased stem diameter (8 WAP). Plants treated with PHMC 3 application were found to have significantly higher number of leaves than those treated with PHMC 2 application at 6 WAP. Plant height, number of leaves, and weight, length, and circumference of main cob of plants treated with 50%R synthetic fertilizer were higher than those of plants treated with 0%R and 25%R synthetic fertilizer. Meanwhile, plants treated with 75%R synthetic fertilizer were found to have better values for girth, leave width, flowering time, harvesting time, number of cobs, dry weight of shoots and roots, grain total soluble solids (TSS) content, and cobs weight than those of plants treated with 0, 25, and 50%R synthetic fertilizer. Key words: sweet corn, multiple liquid biofertilizers, TSS, synthetic fertilizer.